IMPLEMENTASI GURU DALAM MENGATASI KESULITAN KETERAMPILAN BERBICARA SISWA PADA PEMBELAJARAN BAHASA INDONESIA KELAS IX D DI MTs MUHAMMAD BASIUNI IMRAN SAMBAS TAHUN PELAJARAN 2024/2025 - Osama; Aslan Aslan; Effiyadi (ADIBA : JOURNAL OF EDUCATION, 2026)
This study aims to reveal three main aspects: (1) the difficulties experienced by students in speaking skills during Indonesian language learning in class IX D at MTs Muhammad Basiuni Imran Sambas in the 2024/2025 academic year; (2) the factors that cause these difficulties; and (3) the teacher’s strategies in overcoming students’ speaking challenges. This research employed a qualitative approach with a descriptive qualitative design. Data were collected through interviews, observations, and documentation, while data analysis included data reduction, data presentation, and conclusion drawing. The findings indicate that the main difficulty faced by students lies in limited vocabulary, which affects their ability to choose appropriate words when speaking. The contributing factors include psychological aspects, such as low self-confidence, and environmental influences, particularly the frequent use of local languages instead of Indonesian in daily communication. Teachers play a crucial role in addressing these issues by implementing a direct teaching strategy. This strategy focuses on teacher-centered learning with structured steps such as explanation, demonstration, practice, and direct feedback. Through this approach, students become more active and confident in developing their speaking skills)